Management practices for West syndrome in South Asia: A survey study and meta‐analysis. Issue 3 (11th August 2020) - Madaan, Priyanka; Chand, Prem; Linn, Kyaw; Wanigasinghe, Jithangi; Lhamu Mynak, Mimi; Poudel, Prakash; Riikonen, Raili; Kumar, Amit; Dhir, Pooja; Negi, Sandeep; Sahu, Jitendra Kumar
Abstract: Objectives: Considering the dearth of literature on West syndrome (WS) from South Asian countries, this study aimed to evaluate the management practices in South Asia by an online survey and meta‐analysis. Methods: An online questionnaire was sent to 223 pediatric neurologists/pediatricians in India, Pakistan, Myanmar, Sri Lanka, Bhutan, Nepal, and Bangladesh. Their responses were evaluated and supplemented by a meta‐analysis. Results: Of 125 responses received (response rate: 56%), around 60% of responders observed male preponderance and an approximate lead‐time‐to‐treatment (LTTT) of 4‐12 weeks. The commonest etiology observed was a static structural insult (88.6% of responders). Most commonly used first‐line drug (country‐wise) was as follows: India—adrenocorticotropin hormone (ACTH, 50%); Pakistan—oral steroids (45.5%); Myanmar, Sri Lanka, and Nepal—oral steroids (94.4%); Bangladesh—ACTH (2/2); Bhutan—vigabatrin (3/5). ACTH and vigabatrin are not available in Myanmar and Nepal. The most commonly used regime for ACTH was maximal‐dose‐at‐initiation‐regime in India, Sri Lanka, and Bangladesh and gradually escalating‐regime in Pakistan. Maximum dose of prednisolone was variable—most common response from India: 3‐4 mg/kg/d; Pakistan, Bhutan, and Bangladesh: 2 mg/kg/d; Sri Lanka, Nepal, and Myanmar: 5‐8 mg/kg/d or 60 mg/d. The total duration of hormonal therapy (including tapering) ranged from 4 to 12 weeks (67/91). Most responders considered cessation of spasms for four weeks as complete response (54/111) and advised electroencephalography (EEG; 104/123) to check for hypsarrhythmia resolution. Difficult access to pediatric EEG in Bhutan and Nepal is concerning. More than 95% of responders felt a need for more awareness. The meta‐analysis supported the preponderance of male gender (68%; confidence interval [CI]: 64%‐73%), structural etiology(80%; CI 73%‐86%), longer LTTT (2.4 months; CI 2.1‐2.6 months), and low response rate to hormonal therapy(18% and 28% for ACTH and oral steroids respectively) in WS in South Asia. Significance: This study highlights the practices and challenges in the management of WS in South Asia. These include a preponderance of male gender and structural etiology, a longer LTTT, difficult access to pediatric EEG, nonavailability of ACTH and vigabatrin in some countries, and low effectiveness of hormonal therapy in this region.